DIGITALIZATION OF MICRO, SMALL & MEDIUM ENTERPRISES (MSMEs) IN EAST JAVA, INDONESIA - Muhammad Sri Wahyudi Suliswanto; Mochamad Rofik (Muhammadiyah International Journal of Economics and Business, 2019)
This study attempts to provide an overview of the digitalization of MSMEs in East Java. It is a qualitative descriptive study in which the data were collected through surveys with simple random sampling method. Basically, 80 percent of MSMEs have integrated digital literacy, particularly in the context of product marketing, into their strategy, yet only 12 percent have carried out it professionally. In East Java, 70 percent of MSMEs emphasize digital marketing through social media platforms, i.e., Instagram and Facebook, while 30 percent prefer mixed method. This study also reveals that either using a single platform or multi platform, it statistically has insignificant effect on the ratio of online transactions. Nevertheless, there is a significant positive effect between the ratio of online transactions and the management quality of digital marketing.